Motor And Emotional attitudes of Primary School Pupils Towards Participating in Competitive Activities During Physical Educations Lesson - Hosni, Thayn (Journal of Physical Education, 2018)
Motor And Emotional attitudes of Primary School Pupils Towards Participating in Competitive Activities During Physical Educations LessonCompetitive physical activities are considered a necessity for primary school pupils due to their great importance in developing an individual’s personality. The research aimed at concentrating in the importance of competitive activities in learning motor skills in physical education class. The subjects were (442) primary school pupils. The researcher concluded their educational attitude towards competitive activities during physical education lesson although there are some negative attitudes towards such activities. He recommended changing the aim of these competitive activities so as they would not revolve about winning only but also providing the pupil with creative competitive experience.